The Role of Non-Financial Information Sentiment in Shaping Capital Market Reactions - Niedzielska, Ewelina (2025)
The monograph is devoted to analyzing the role of non-financial information in shaping the reactions of the capital market. The discussion is framed within two competing theoretical approaches. The first is the efficient market hypothesis, which assumes that incoming data are fully and immediately reflected in the prices of financial instruments. The second approach is represented by behavioral finance, which emphasizes the importance of cognitive heuristics and asymmetries in information processing. At the same time, journalists and online media are gaining increasing significance, becoming an important source of economic knowledge. Moreover, the dynamic growth of global data resources, particularly textual data, has made sentiment analysis an essential tool for identifying factors influencing investors’ decisions. The monograph combines theoretical and empirical objectives. On the cognitive level, it focuses on identifying and characterizing the key paradigms and concepts that explain the mechanisms of information generation, transmission, and reception in the capital market. On the empirical level, it addresses the assessment of how investors discount information, with particular attention to the sentiment of press articles concerning companies listed on the Warsaw Stock Exchange. The analysis covered more than 56,000 English-language press publications from 2013 to 2022, applying a dictionary-based approach and the event study method to evaluate market reactions. The findings confirm the existence of asymmetry in investors’ responses to positive and negative news, demonstrating that press sentiment is a significant factor in explaining market behavior, while also contributing to the debate on the interaction between neoclassical and behavioral perspectives in finance.
Keywords: capital market; stock exchange; text analysis; textual sentiment; financial journalism